(untitled) (Journal of Shaheed Suhrawardy Medical College, 2023)
Background: Poisoning is a global issue occurring all over the world involving people of all ages and genders, from all ethnic and economic groups. It is estimated, there are 1 to 5 million cases of Organophosphorus poisoning per year worldwide with approximately 300,000 deaths. Aim of the study: To assess the demographic pattern of death due to organophosphorus poisoning with respect to age, sex, occupation, education, and socioeconomic status. Materials and Methods: A retrospective study was conducted by the department of Forensic Medicine, Sheikh Hasina Medical Colleges, Tangail, from January 2020 to December 2020. Result and discussion: 85(20.68%) were due to poisoning, out of those poisoning cases 77 (90.58%) were due to organophosphorus compound poisoning. The incidence was higher in females (51.94%) than in males. 90.00% of the victims in our study were married females, and 63.64% of cases were below Secondary education. Among the male deaths 83.78% were from rural areas, female rural deaths were 82.50%. Housewife (38.9%) were the major victims. Conclusion: Illiteracy, Poverty, Cheap availability of organophosphorus compounds, lack of employment, and stressful lifestyle were the common reasons behind suicidal poisoning. Health education of farmers, other agricultural laborers, and young people about the toxic and detrimental effects of organophosphorus compounds will help in preventing suicidal and accidental poisoning to some extent. J Shaheed Suhrawardy Med Coll 2022; 14(1): 62-64